On-line Analytical Processing (OLAP) Operation for Outpatient Healthcare - Talib M. J. Al Taleb; Sami Hasan; Yaqoob Yousif Mahd (Iraqi Journal of Science, 2021)
This paper presents an architecture for the data warehouse of outpatient healthcare (DWOP) as a data repository collects data from two different sources (Databases of outpatient healthcare and Excel files from hospitals) and provides storage, functionality and responsiveness to queries to meet decision makers requirements.Successfully supporting managerial decision-making is critically dependent upon the availability of integrated, high quality information organized and presented in a timely and easily understood manner. â€œOn-Line Analytical Processing (OLAP) is utilized for decision support to get interesting informationâ€ from the data warehouse with a rapid execution time. OLAP is considered one of Business Intelligence tools.